PENGARUH TOTAL ASET, TINGKAT SOLVABILITAS, OPINI AUDIT, PROFITABILITAS DAN JENIS INDUSTRI TERHADAP AUDIT DELAY (Studi Empiris Pada Perusahaan Manufaktur dan Multifinance yang Terdaftar di Bursa Efek Indonesia Tahun 2013-2017) - Nadya Arindini Pratiwi; Muhammad Rasuli; Fajar Odiatma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2019)
This research was aimed to examine the effect of total assets, solvencylevel, audit opinion, provability, and type of industry on audit delay inmanufacturing sub-sector food, beverage and textile and multifinance companieslisted on Indonesia Stock Exchange 2013-2017. The technique of sampilng usingpurposive sampling is the population used as sample in the study is the populationthat meets the criteria sample. From these criteria, we got sample of 28manucafturing and multifinance companies in Indonesia Stock Exchange 2013-2017. Hypothesis testing using multiple linear regression. However, these test arecarried out after the test meet the classical assumptions of normality,multicollinearity, heteroscedasticity, and autocorrelation test. The result of thisresearch prove that the total asset, solvency level, type of industry have significanteffect to audit delay. Provability and audit opinion has no significant effect toaudit delay. The result of determination coefficient of R2 found that 27,7% formindependent variabel in this research able to influence dependent variabel, whilethe rest 72,3% influenced by other variabel not examined in this research.Keywords : audit delay, total assets, solvency level, audit opinion, provability,and type of industry